2016
DOI: 10.19082/3385
|View full text |Cite
|
Sign up to set email alerts
|

Intention of Continuing to use the Hospital Information System: Integrating the elaboration-likelihood, social influence and cognitive learning

Abstract: IntroductionAnticipating effective factors in information system acceptance by using persuasive messages, is one of the main issues less focused on so far. This is one of the first attempts at using the elaboration-likelihood model combined with the perception of emotional, cognitive, self-efficacy, informational and normative influence constructs, in order to investigate the determinants of intention to continue use of the hospital information system in Iran.MethodsThe present study is a cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Extensive research has been conducted regarding the acceptance of and intention to use medical information technology [1215]. Previous studies focused on certain characteristics of the behavioral intention regarding the use and acceptance of the information system by healthcare professionals [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted regarding the acceptance of and intention to use medical information technology [1215]. Previous studies focused on certain characteristics of the behavioral intention regarding the use and acceptance of the information system by healthcare professionals [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The construction of perceived value to the user is caused by information quality, and this perceived value then affects the user's satisfaction (Yanuar and Ari, 2018). Several studies have previously confirmed the impact of information quality on patient satisfaction (Ho et al, 2019;Farzandipour et al, 2016). Further research revealed that HIS system quality is related to user (patient) satisfaction (Yu and Shih-Chieh, 2013;Maryam and Khaled, 2015;Gustavo and Antonio, 2015;Scheepers et al, 2006;Coombs et al, 2001;Teo and Wong, 1998).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Few studies have thoroughly evaluated the professional acceptance of or satisfaction with health information technology through assessment instruments or theoretical models, such as the Technology Acceptance Model 3 (TAM3) or the integrating service quality with system and information quality (3Q) model [ 24 , 57 ]. Extensive research has explored user perceptions of using medical information technology [ 9 , 58 62 ], which has still not been implemented.…”
Section: Introductionmentioning
confidence: 99%